Genotypic distribution of TT virus (TTV) in a Czech population: evidence for sexual transmission of the virus - Krekulova, L; Rehak, V; Killoran, P; Madrigal, N; Riley, L W (Journal of clinical virology, 2001)
BACKGROUND: TTV is a new DNA virus distinguished by its high degree of strain heterogeneity. The geographic clustering of viral genotypes suggests frequent community transmission. While no specific human disease has yet been linked to it, a transmission mechanism that facilitates strain diversity may eventually select for a strain that will become pathogenic. OBJECTIVE: This study was performed to examine the prevalence, genotypic distribution, and mode of transmission of TTV in detail. STUDY DESIGN: Three groups of study subjects were recruited between October 1998 and January 2000 in Prague, Czech Republic. Group 1 included 152 injection drug users with liver disease; group 2 included 102 persons with liver disease who denied ever using injection drugs; group 3 included 111 prospective blood donors. TTV DNA was detected from blood by a semi-nested PCR assay, and a selected set of PCR products was genotyped by direct sequencing. Factors associated with TTV prevalence in groups 1 and 2 subjects were compared. RESULTS: TTV was detected in 15.8, 13.7, and 13.5% of Groups 1, 2, and 3 subjects, respectively (P>0.05). The most common genotype was 2 (54%), followed by 1 (13%). The prevalence of TTV viremia was nearly three times higher in persons with a present or past history of hepatitis B compared to those without (P<0.05). TTV prevalence increased proportionately with the number of lifetime sex partners in both groups (P<0.05); it was highest (32%) among non-users of injection drugs who had five or more lifetime sex partners. CONCLUSION: TTV prevalence in the Czech population is similar among blood donors, persons with liver disease, as well as in a high-risk population of injection drug users. TTV appears to be sexually transmitted.
Keywords: sexuální chování; dospělí; Sexually Transmitted Diseases; infekce DNA virem; Sexual Behavior; Genotype; DNA virů; Adolescent; přenos infekční nemoci; Female; DNA Virus Infections; Česká republika; Disease Transmission, Infectious; mužské pohlaví; dárci krve; rizikové faktory; Blood Donors; Hepatitis B; lidé; hepatitida B; Czech Republic; genotyp; ženské pohlaví; Risk Factors; Humans; sexuálně přenosné nemoci; Torque teno virus; Substance Abuse, Intravenous; Male; intravenózní abúzus drog; Adult; mladiství; DNA, Viral